A case of nearly complete response in hepatocellular carcinoma with disseminated lung metastasis by combination therapy of nivolumab and ipilimumab after treatment failure of atezolizumab plus bevacizumab - Hyung Jun Kim; Sang Youn Hwang; Jung Woo Im; Ki Jeong Jeon; Wan Jeon (Korean Liver Cancer Association, 2023)
Recently, the efficacy of immuno-oncologic agents for advanced hepatocellular carcinoma (HCC) has been proven in several trials. In particular, atezolizumab with bevacizumab (AteBeva), as a first-line therapy for advanced HCC, has shown tremendous advances in the IMBrave150 study. However, second or third-line therapy after treatment failure with AteBeva has not been firmly established. Moreover, clinicians have continued their attempts at multidisciplinary treatment that includes other systemic therapy and radiotherapy (RT). Here, we report a case that showed a near complete response (CR) of lung metastasis to nivolumab with ipilimumab therapy after achieving a near CR of intrahepatic tumor using sorafenib and RT in a patient with advanced HCC who had experienced treatment failure of AteBeva.